A Time Motion and Analysis of Partnering Skills in Latin-American Dance Using a Semi-Automatic Tracking System: A Case Study - Petra Zaletel (Journal of Anthropology of Sport and Physical Education)
The aim of the research was analysing motion and partnering skills by examining different relation positions between dance partners, distance covered and speed of movement in Latin-American dance. The sample consisted of three elite Latin-American dance couples simultaneously danced each of five Latin dances consecutively. Dances were recorded using two cameras - first was used to determine the path of the dancers’ movement (secured to the ceiling of the hall), the second camera was located on the side of the dance floor to facilitate annotation of the dancers’ posture relationships. The overhead footage was later transferred to a PC and analysed with the tracking system. With a specifically designed annotation system we categorised five different relationship postures exhibited between male and female dancers. We used two-way ANOVA for establishing differences in motion regarding gender and different dances. Results showed no differences between gender, but significant differences in speed and distance covered between dances. Samba and Passodoble seemed to be the most dynamic dances, with longest distance covered and highest speed of movement, followed by Cha Cha and Jive whereas activity in the Rumba took place in a relatively small area of the dance floor. Dancers were in open positions 99% of the time (except Passodoble – 87% and Cha Cha – 91%), either touching or not touching each other, with focus on the partner evident between 40% and 60% of the time in all dances. These findings tended to confirm rather than dispute the apriori expectations of individual dance choreographies.